Integrated Audit Environmental System; Optimalisasi Peran Bpk Guna Mewujudkan Good Policy System Dalam Pembangunan Ekonomi Indonesia - Dararida Fandra Mahira; Aura Ning Istanti; Ilham Khalid Lubis (STAATSRECHT: Indonesian Constitutional Law Journal, 2018)
Abstract.The Supreme Audit Agency (BPK) is a state institution that has a role in upholding the principles of good governance. One that is rarely known to the public is the principle of environmental protection. Despite the role of the BPK in upholding principles, such as regulating positive activities, or providing reports on the results of environmental audits. However, it turns out that the position is not as effective as expected, because the BPK Institution only has 16 certified international environmental auditors, while its duties are related to the environment that is spread throughout the territory of Indonesia. Therefore, the author seeks to provide an effective solution to the concept of reform, namely synergizing the BPK Institution with the relevant Ministries, including the wider community, as well as non-governmental organizations. The author conducted a study based on data on the state of the legal environment, welfare, and environmental audits, then visualized in a frame of mind. With the formulation of the concept of BPK synergy with several relevant Ministries, it is expected to be able to uphold social and environmental welfare, and be able to reduce the country's economic losses.Keywords: Environmental Audit, Republic of Indonesia BPK, Integrity, Social Welfare Abstrak.  Badan Pemeriksa Keuangan merupakan Lembaga negara yang memiliki peran menegakkan prinsip tata kelola pemerintahan yang baik. Salah satu yang jarang diketahui publik adalah prinsip perlindungan lingkungan. Meskipun adanya peran BPK dalam menegakan prinsip, seperti mengatur aktivitas positif, atau memberikan laporan hasil audit lingkungan. Namun ternyata kedudukannya tidak seefektif yang diharapkan, karena Lembaga BPK hanya memiliki 16 auditor lingkungan internasional bersertifikat, sedang tugasnya berkaitan dengan lingkungan yang tersebar di seluruh wilayah Indonesia. Oleh karena itu, penulis berupaya memberikan solusi efektif dengan konsep reformasi, yaitu mensinergikan Lembaga BPK dengan Kementerian terkait, termasuk masyarakat luas, dan juga organisasi non-pemerintah. Penulis melakukan kajian berdasarkan data pada keadaan lingkungan hukum, kesejahteraan, dan audit lingkungan, kemudian divisualisasikan dalam kerangka berpikir. Dengan formulasi konsep sinergi BPK dengan beberapa Kementerian terkait, diharapkan dapat menegakkan kesejahteraan sosial dan lingkungan hidup, serta dapat mengurangi kerugian ekonomi negara.Kata Kunci: Audit Lingkungan, BPK RI, Integritas, Kesejahteraan Sosia